Safeguarding planetary health for Southeast Asia's future children - Jemilah, Mahmood *; Guinto, Renzo R; Lacey-Hall, Oliver; Faiesall, Maisarah; Poppema, Sibrandes *; Lee, Elizabeth * (Elsevier, 2022)
While we continue to deal with the ongoing COVID-19 pandemic, the past months have also revealed the sorry state of our collective planetary health, including in southeast Asia. Weeks after the 2021 UN climate change conference (known as COP26), Malaysia experienced intense flooding at a scale that has never been seen before,1 while the Philippines was once more hit by a super typhoon that killed hundreds and displaced a hundred thousand more.2 In the beginning of 2022, the Stockholm Resilience Centre announced that a fifth planetary boundary has already been breached—chemical pollution, particularly plastic—in addition to climate change, land use change, disrupted biogeochemical flows, and biodiversity loss.3 Southeast Asia is central source of plastic pollution, as most of the top five plastic-polluting countries are located in the region.4 Furthermore, as a biodiversity hotspot, the jungles of southeast Asia offer ideal conditions for another potential zoonotic outbreak, and it is vital to prevent future pandemics at the source.5